VERS LA PROFESSIONNALISATION DE LA GESTION SCOLAIRE EN CÔTE D’IVOIRE: UNE CONTRIBUTION DES ACTEURS DE L’ENSEIGNEMENT TECHNIQUE ET PROFESSIONNEL - Gbongué Jean-Baptiste (European Scientific Journal, ESJ, 2015)
The study aims at describing and at having a critical look on the management of the professional and technical secondary establishments of Cote d’Ivoire with the aim of its professionalization. It draws up the current state of this management to improve it if necessary. One of the most recent developments in this domain suggests four big dimensions of the professionalization: complicated tasks and high skills, specific and recognized status, scientific and practical knowledge copies, training and socialization. The article documents these aspects. To answer the questions raised by this study and to reach the goal which aims, 196 school actors (124 men and 72 women) participated in the research. Twenty (20) focuses group or newsgroups help to collect relevant information with the guarantors. The results reveal at the same time an overdrawn perception, a pessimist of the current state of the management in these schools and a concern to contribute to improve this state in terms of a real professionalization. In brief, in context of globalization of the requirements of the quality of education, the professionalization seems to stand out as an imperative. Such a reflection turns out fundamental for the Ivoirian education system which makes a commitment in deep educational reforms. The results indicate especially that on the way of the desired professionalization, important challenges remain to raise.